Brahmi Inscriptions from Kondane Caves. (20th April 2017) - Mokashi, Rupali; Samel, Pankaj Vijay
The aim of the paper is to analyze the Brahmi inscriptions engraved at Kondane caves. All the previous research works have recorded and studied only one donation that was made by Balaka, a disciple of Kanha. Apart from this inscription, three more inscriptions have been noted. In our quest to search them we could locate only one in situ that has been photo documented and analyzed.